HONDURAS-BRASIL: UN SIGLO DE AFINIDADES ELECTIVAS, DE SOLIDARIDAD Y DE COOPERACIÓN PARA EL DESARROLLO (1906-2007) - Domínguez Avila, Carlos Federico (2008)
This article delves into the economic and political relations held in the course of a century by Honduras and Brazil in the period between 1906 and 2007. More specifically, the author points out the particularities, changes and consistencies of such relations, as well as the factors that mediated in their historical configuration, such as the assigned and self-assigned role of each country in the Latin American and world economy, the impact caused by the United States as the supreme continental power, and the internal and regional political changes.